Educational policies from the perspective of school inclusion in Brazil (Research, Society and Development, 2022)
The article aims to reflect on the process of school inclusion of students with deafness in regular education from Brazilian normative documents, seeking to understand which documents guide the perspective of school inclusion in Brazil. The analyzes took place from the following questioning: how are the propositional documents in the perspective of school inclusion treating the education of the deaf? To answer the question, we searched in the documents of Brazilian educational policies for referrals in relation to the inclusive perspective from 1988 to 2020, highlighting the propositional documents for the education of deaf people. It is configured as a longitudinal study, document, and discourse analysis. For the analysis of the documents, Shiroma, Campos, and Garcia (2005) and Evangelista (2009) were used and for the analysis of the discourse we sought the studies of Orlandi (2007). When analyzing the documents, we found that educational policies from the perspective of inclusive education in Brazil have changed since 1990, influenced by international documents, such as declarations and conventions and with the approval of the National Education Plan in 2014, the propositions have changed, especially, in relation to the schooling of people in the public of special education that open to be carried out in schools and specialized classes, modifying the referrals in relation to the education of this population.